Pengaruh DER, TATO dan NPM Terhadap Kebijakan Dividen (Studi Kasus Pada Industri Dasar dan Kimia yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2012-2016) - Iwan Firdaus; Putri Handayani (JAAF (Journal of Applied Accounting and Finance), 2019)
This research was conducted to examine the effect of Debt to Equity Ratio (DER), Total asset turnover (TATO) dan Net profit margin (NPM) to Dividend Payout Ratio (DPR). The object for this research is basic industry and chamicals listed on the Indonesia Stock Exchange in the period 2012-2016. This research was conducted using quantitative menthod with total 10 sample of research were determined by saturated sampling. Method of hypothesis testing using t-test. This research use Debt to Equity Ratio (X1), Total asset turnover (X2), Net profit margin (X3) as independent variable and Dividend Payout Ratio as dependent variable. The results of this research is Total asset turnover (TATO) and Net profit margin (NPM) positive and has significant effect to Dividend Payout Ratio, while the DER negative and has no significant effect to Dividend Payout Ratio.